Quality management practices, organizational learning, organizational culture and organizational performance in Iraqi higher education institution: an instrument design - Mohammed, Ahmed Hani; Taib, Che Azlan; S.R. Nadarajan, Santhirasegaran (Serials Publications, 2016)
The business services environment are experiencing intense competition.Hence, higher education facing series of challenges in order to improve organizational performance, and an ability of competition.The same situation was happened to Iraq’s higher education.As an effort for strengthening the teaching, research and consultation activities to enhance the quality performance, quality management practices (QMPs) is one of the important factors affecting the organizational performance.Similarly, some emphasis was placed on organizational learning (OL) as another tool to support organizational performance.In addition, the reference to the organizational culture (OC) based on the results of the performance affected by environmental surroundings for educational institutions.The combination of these three elements: QMP, OL and OC finally affected the performance of higher education.Therefore, the aim of this paper is to explain a preliminary about the role of these factors on the affecting of the performance of higher education institutions in Iraq.This paper proposed the measurement instrument for measuring higher education performance, therefore the development and validation of the quantitative instrument (questionnaire) towards measuring the performance also discussed.In addition, the reliability of the constructs is also being explained.